Aspects of titanium-implant surface modification at the micro and nano levels - Milinković, Iva (Materiali in tehnologije, 2012)
The shape and chemical composition, as well as the macro- and microtopography, of an implant surface have been studied widely as the major factors that positively influence implant osseointegration. Titanium and titanium alloys have been used extensively over the past 20 years as biomedical materials in orthopedic and dental surgery because of their good mechanical properties, corrosion resistance, no cell toxicity, and very poor inflammatory response in peri-implant tissue, which confirms their high biocompatibility. Their favorable biological performance is attributed to a thin native oxide film that forms spontaneously on the titanium surface. It is well established that surface roughness plays an important role in implant fixation. Accordingly, some authors have indicated the existence of an optimal range of surface roughness. The titanium surface can be either chemically or physically modified, or both, in order to improve biomaterial-tissue integration. Different treatments are used to modify the titanium surface. Hydroxyapatite coatings, preceded or not by acid etching, are used to create a rough, potentially bioactive surface. Oxide blasting treatments, either with or without chemical etching, are used to develop roughsurfaces. Thick oxide films obtained by anodic or thermal oxidation have been used to accelerate the osseointegration process. The ideal microtopography of the surface is still unknown, however, because it is very difficult to associate surface properties with clinical results. As more accurate knowledge is required, several Ti surfaces have been analyzed and the endosseous implant surface modified on the micro level has been thoroughly studied. Additionally, the production of gold (Au) nanoparticles to be added to the micron-scale modified surface has been performed. In this respect, an appropriate overview of our results is given.
Keywords: implantat; implantati; titan alloys; titanove zlitine; modifikacija površine; surface modification; microstructure; mikrostruktura